Nonentagled qutrits in two way deterministic QKD - Shamsul Shaari, Jesni; Wahiddin, Mohamed Ridza (Elsevier, 2007)
We consider the use of qutrits in a two way deterministic quantum cryptographic protocol which exhibits a higher level of security. We analyse the security of the protocol in the context of the Intercept Resend Strategy. The protocol which transmits a qutrit is naturally limited to not utilising all the available maximally overlapping basis due to a no go theorem not unlike the universal-NOT. We further propose another protocol to generalise the protocol above against the no-go theorem.